Pemeriksaan Keimigrasian Di Perbatasan Darat Indonesia Dari Perspektif Borderscapes, Geopolitik, Dan Biopolitik - Arianto, Ari; Septiyanto, Deni; Hidayat, Fadil; Kamil, Farhan (Jurnal Kajian Stratejik Ketahanan Nasional, 2022)
Borderscapes is a new way to view the border shared between two nations. Borderscapes is a view that tries to combine a more people-oriented view and Michel Foucault’s biopolitics. Borderscapes emphasize on the conditions for people who live on the border between two nations and on both sides of the border, such a view makes borderscapes share a lot of similarities with a new paradigm of how border should be treated called soft border. With this new way to view borders, new challenges and opportunities arise caused by the border between two countries and by people who live on the border between the two countries. Keywords: Borderscapes, National Border, Immigration check